PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) PADA PEMBERIAN KOMPOS KULIT KOPI DAN PUPUK ORGANIK CAIR NASA - Wiraningsih, Komang Ayu; Bahrudin, Bahrudin (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The purpose of the study was to investigate the effect of adding coffee husk compost and Nasa liquid organic fertilizer (LOF) on the growth and yields of cayenne pepper plants. The research was conducted in Bakti Agung Village, Poso District, from November 2020 to February 2021. The study utilized a two-factorial randomized block design (RBD). The first factor was control (K0), 25 g coffee husk compost (K1), 50 g coffee husk compost (K2), 75 g coffee husk compost (K3), and 100 g coffee husk compost (K4). The second factor was control (P0) and 4 ml Nasa/l water (P1). Therefore, there were 10 treatment combinations. Five plants were grown in each experimental unit. The findings revealed that there was no significant interaction effect between the application of coffee husk compost and Nasa LOF on all parameters observed. However, the individual effect of the K3 treatment demonstrated a better plants growth of cayenne pepper in all observation parameters. Similarly, the individual effect of the P1 treatment showed larger fruit number and weight.